2021
DOI: 10.1140/epjd/s10053-021-00077-9
|View full text |Cite
|
Sign up to set email alerts
|

Confined H$$^-$$ ion within a density functional framework

Abstract: Ground and excited states of a confined negative hydrogen ion have been pursued under Kohn-Sham density functional approach by invoking a physically motivated work-function-based exchange potential. The exchange-only results are of near Hartree-Fock quality. Local parameterized Wigner-type, and gradient-and Laplacian-dependent non-local Lee-Yang-Parr functionals are chosen to investigate the electron correlation effects. Eigenfunctions and eigenvalues are extracted by using a generalized pseudospectral method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In our specific investigation, the application of DFT played a pivotal role in probing numerous essential parameters related to electronic behavior, energetics, thermodynamics, and adsorption tendencies, notably focusing on binding energy. Additionally, it aimed to unravel the reactivity of pharmacological complexes through quantum molecular descriptors such as the Highest Occupied Molecular Orbital (HOMO), Lowest Unoccupied Molecular Orbital (LUMO), band gap energy, chemical hardness, softness, electronegativity, and electrophilicity 36–39 . These descriptors are fundamental in comprehending the behavior and potential applications of these compounds in pharmacology.…”
Section: Methodsmentioning
confidence: 99%
“…In our specific investigation, the application of DFT played a pivotal role in probing numerous essential parameters related to electronic behavior, energetics, thermodynamics, and adsorption tendencies, notably focusing on binding energy. Additionally, it aimed to unravel the reactivity of pharmacological complexes through quantum molecular descriptors such as the Highest Occupied Molecular Orbital (HOMO), Lowest Unoccupied Molecular Orbital (LUMO), band gap energy, chemical hardness, softness, electronegativity, and electrophilicity 36–39 . These descriptors are fundamental in comprehending the behavior and potential applications of these compounds in pharmacology.…”
Section: Methodsmentioning
confidence: 99%
“…Salen ligands (H 2 L SAL )/(H 2 L RSAL ), (SAL = salicylaldehyde, R = substituted group), which are well-received Schiff bases (SBs) containing nitrogen (N) and oxygen (O) donor atoms, have been extensively researched over the last few years due to their ubiquitous properties 1 and wide range of physicochemical characteristics. [2][3][4][5][6][7] The ligands' N/O-donor atom versatility makes stabilizing components via complex formations across multiple oxidation states. 4,5,8 Furthermore, a recent eye-catching trend is investigating (H 2 L SAL )/(H 2 L RSAL )-metal complexes or coordination polymers (CPs) electrical conductivity and charge transport properties [9][10][11][12][13][14] (Scheme S1 †).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, atoms confined in zeolite traps, cluster, in fullerene cages can also be analyzed using the quantum confined model [11][12][13][14][15]. In these previous researches, people mainly focus on the study of the physical properties of confined atoms and molecules, such as the wave function, probability density, energy level structure, the electric dipole polarizabilities, hyperfine splitting constants, etc [16][17][18][19][20][21][22]. It has been shown that due to the quantum confinement effect, the physical properties of the confined systems are significantly changed.…”
Section: Introductionmentioning
confidence: 99%